Poverty, Inequality, and Growth in Urban China, 1986-2000 - Xin Meng; Robert Gregory; Youjuan Wang (Institute for the Study of Labor (IZA), 2005)
Although urban China has experienced spectacular income growth over the last two decades, increases in inequality, reduction in social welfare provision, deregulation of grain prices, and increases in income uncertainty in the 1990s have increased urban poverty. Using a large repeated cross-section household survey data from 1986 to 2000, this study maps out the change in income, inequality, and poverty over the 15 year period and investigates the determinants of poverty. It is found that the increase in the poverty rate in the 1990s is associated with the increase in the relative food price, and the need to spend on education, housing and medical care which were previously paid by the state. In addition, the increase in the saving rate of the poor due to an increase in income uncertainty contributes significantly to the increase in poverty measured in terms of expenditure. Even though income growth reduces poverty, the radical reform measures implemented in the 1990s have sufficiently offset this gain that urban poverty is higher in 2000 than in 1986.
Keywords: O15; O40; D31; I31; 330; poverty; income growth; inequality; China; Städtische Armut; Einkommensverteilung; Einkommen; Wirtschaftswachstum; Sozialreform; Nahrungsmittelpreis; China